Audit Performance Measurement Model and the Main Areas of Performance Management - Domokos, László; Weltherné Szolnoki, Dóra (Public Finance Quarterly, 2020)
Profit-oriented business sector and public-sector budgetary institutions using public funds differ in many aspects, but their common feature is that the responsibility for performance- and quality-oriented management shall prevail. One element of this is that the management identifies and manages intentional action, that is, plans, directs, measures, analyses, and puts information into a decision-making system in order to operate and perform its tasks. However, it is not easy to identify the criteria of the required performance in the processes of institutions performing specific public tasks, as many aspects have to be met simultaneously, such as: good governance, good organisational management, economical, effective and efficient operation, quality-driven operation, creation of added value and the utilisation of professional activities. This study demonstrates how the management tools of performance management contribute to organisational performance efficiency that also meet the aforementioned criteria.